Isolation, Characterisation And Bioefficacy Analysis Of Bacillus Thuringiensis (Bt) Strains Against Dengue Vectors - Ho, Lai Yee (2021)
A mounting public health concern over mosquito-borne diseases, a global economic burden, and failure of current control measures due to escalating development of insecticides resistance have intensified the search for alternative ecofriendlier vector control strategies. An investigation was conducted to explore the toxicity profiles of indigenous B. thuringiensis isolates from an ex-tin mining area. Verification was performed through microscopic identification and biochemical characterisations. Morphological features of the crystal proteins were assessed using scanning and transmission electron microscopy. Distribution of insecticidal genes and crystal protein classes were examined through PCR and SDS-PAGE analyses. Eventually, these isolates were screened for larvicidal and sublethal efficacies against laboratory strains of Ae. albopictus and Ae. aegypti. From the seven sampling sites, 13 B. thuringiensis isolates were obtained (A10C, D10D, N6Bss, 6a3s, 8a3, 8a3s, 8b3, R1, R2, R3, D1C, A2B and C6D) with an overall B. thuringiensis index of 0.07. Spherical-shaped crystal proteins were present in all isolates, while lesser numbers of ovoidal- and cuboidal-shaped crystal proteins were noted. Protein profiles revealed presence of eight classes of crystal proteins (Cry2, Cry4C/4D, Cry6A, Cry10, Cry11, Cry34, Cry35, Cyt1/2). Four of the isolates (N6Bss, 8a3, R1 and A2B) harboured all six of the examined insecticidal genes (cry1, cry2, cry4, cry10, cry11 and cyt2), which are known to produce Dipteran-specific delta-endotoxins.